The Relationship of Hemoglobin Levels with Menstrual Patterns in Adolescent Girls at Surakarta - Nahdiyah Karimah; Dyah Krisnawati Satia Pratiwi; Emma Anastya Puriastuti (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2024)
Adolescent girls are susceptible to anemia because they bleed during menstruation. If it continues into pregnancy, anemia can cause the fetus to experience stunting in the future. The percentage of stunted babies and toddlers in Indonesia in 2021 will reach 24.4%. This study aims to determine the relationship between hemoglobin levels and menstrual patterns in adolescent girls. This research is a quantitative observational research with a cross sectional research design. The sampling technique used Cluster Random Sampling with a sample size of 76 respondents. Data analysis used the Pearson Correlation Test and Spearman Correlation Test. Based on the research results, there was no significant relationship between hemoglobin levels and menarche (p value 0.626). There is a significant relationship between hemoglobin levels and menstrual duration (p value 0.0001) and a strong inverse correlation (-0.693). There is a significant relationship between hemoglobin levels and the menstrual cycle (p value 0.0001) and a moderate correlation (0.485). There is a significant relationship between hemoglobin levels and the incidence of dysmenorrhea (p value 0.0001) and a strong correlation (0.691). Female students are advised to maintain diet, rest and exercise patterns so that the hemoglobin formation process is optimal and menstrual patterns are normal.